An ordered categorical response model with endogenous switching: Simulation Exercises and an Application to State Health (2011)
We develop and estimate a full information maximum likelihood ordered categorical response model with endogenous switching. Simulation exercises show that estimated parameters are unbias and consistent. And application to Internet access indicates that there are selection and moral hazard.